English Language in Medical Informatics Teaching: Opinion of Students - Anastasiya V. Andreeva; Ksenia A. Mitrofanova; Valery A. Teleshev; Felix A. Blyakhman (Высшее образование в России)
The paper describes an interdisciplinary experience of teaching one of the modules of medical informatics in English. The interdisciplinary approach was introduced in the Ural State Medical University (USMU). During 2015–2017 academic years, the interdisciplinary team including teachers of the biomedical physics, informatics and mathematics department and foreign languages department of USMU were developing and introducing integrative classes on medical informatics in English. In total, 287 students of general medicine, pediatrics, dentistry and preventive medicine faculties participated in the survey concerning integrative training in medical informatics in English. Evaluation of both foreign language communication skills and abilities to search medical information in international databases was performed during practical studies. 76% of medical students responded positively to the opportunity to improve foreign language communication skills for professional purposes. We find it possible to develop some modules of professional disciplines in English to teach medical students.